A 3D analysis of spatial habitat metrics about the confluence of Negro and Solimões rivers, Brazil. Issue 1 (1st December 2019) - Gualtieri, Carlo; Abdi, Reza; Ianniruberto, Marco; Filizola, Naziano; Endreny, Theodore A.
Abstract: Confluences are integral features in rivers characterized by complex 3D changes in flow hydrodynamics and bed morphology and provide important ecological functions. This paper presents the first known analysis of 3D spatial habitat metrics, based on hydraulic complexity, using data from the Negro and Solimões rivers confluence in the Amazon Basin, during high‐ and low‐flow conditions. The analysis was conducted using two bioenergetics metrics M 2 and M 3 computed for 1‐m 2 cells within each cross section. M 2 is related to the drag force on a fish moving between two locations in the river, whereas M 3 is related to the energy needed by a fish to remain in a location without spinning. M 2 provides useful spatial analysis of the confluence, and its longitudinal distribution as well as its uniformity parameters in the river cross sections showed a peak downstream the junction and a rapid decay in the central confluence hydrodynamic zone. This trend corresponded with the classic hydrodynamic features as well as with literature observed patterns of biotic assemblages downstream of river confluences. At the entrance of the Amazon channel, M 2 peaks corresponded to the largest concentration of fish larvae demonstrating that the metric could be used to identify hot spots for aquatic species richness. The 3D derived M 2 values were larger in magnitude than M 2 values derived from depth‐averaged velocity data. The longitudinal distribution of M 3 metric peaked immediately downstream of the confluence, and the M 3 helical flow cells corresponded with areas where dolphins congregate to feed and could exert less energy to remain in this zone. The study demonstrated that a 3D analysis of velocity gradients is able to reveal and explain observed patterns of species abundance and richness beyond those captured by a 2D analysis.